Formulation of Fungi for Cocoa Pod Waste Decomposition and Cocoa Pod Rot Control (Phytopthora palmivora Butl.) - Kuswinanti, Tutik; Brugman, Eirene; Putri, Nur Annisa; Nurhidayaha, Andi; Nasruddin, Andi (CROPSAVER, 2024)
The development of cocoa in Indonesia was followed by an increase in cocoa waste in the form of fruit skins as much as 75% of fruit skins. The purpose of this study was to determine the formulation of fungi (Trichoderma harzianum and Pleurotus ostreatus)and methods of composting cocoa fruit skin waste as well as analysis of the quality of the compost produced.  The research was conducted at Bontomanai village, Bungayya sub-district, and Gowa district which all have composting facilities on February to June 2023 . The quality testing of compost and counting the amount of Phytophtora palmivora spores in cocoa pod husk compost was carried out in the Plant Disease Laboratory, Department of Plant Pest and Disease, Faculty of Agriculture, Hasanuddin University. This study consisted of three activities, there were producing compost, checking the quality and maturity of the compost, and measuring the amount of P. palmivora spores in the cocoa pod husk compost. This study included six treatments, notably P0: without Bioactivator, open pile, P1: T. harzianum, open pile, P2: P. ostreatus, open pile, P3: T. harzianum + P. ostreatus, open pile, P4: T. harzianum + P. ostreatus, open pile P4: without Bioactivator, close pile, P5: T. harzianum, close pile, P6: P. ostreatus, close pile, P7: T. harzianum + P. ostreatus close pile. Based on the compost maturity test and nutritional content analysis of cocoa waste, it can be seen that the most effective treatment in composting cocoa pod shells was the T. harzianum + P. ostreatus in open pile treatment, the highest levels of P2O5 and K2O but lowest levels of C/N.  Composting process had also reduced the amount of P. palmivora in cocoa pod husk waste.